2021
DOI: 10.1007/s00296-021-04816-4
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of immunoglobulin G4-related disease as subglottic stenosis: a case-based review

Abstract: Background Immunoglobulin G4-related disease (IgG4-RD) is a recently recognized fibro-inflammatory pathology that has been reported to affect principally the retroperitoneum, hepatobiliary system, salivary glands, orbital structures or lymph nodes. However, IgG4-RD with laryngeal involvement is a very rare entity. Our aims were to describe a case of subglottic stenosis as first and only manifestation of IgG4-RD and review the literature. A patient with IgG4-RD affecting the larynx that presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Fibrosis was present in 71% of the cases. In one of the cases obliterative phlebitis was observed, while in another, marked eosinophilic infiltration was noted [4][5][6][7][8][9][10][11][12][13][14]. While lymphocytic infiltration rich in plasma cells, and fibrosis were evident in our case, obliterative phlebitis was not observed.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Fibrosis was present in 71% of the cases. In one of the cases obliterative phlebitis was observed, while in another, marked eosinophilic infiltration was noted [4][5][6][7][8][9][10][11][12][13][14]. While lymphocytic infiltration rich in plasma cells, and fibrosis were evident in our case, obliterative phlebitis was not observed.…”
Section: Discussionmentioning
confidence: 52%
“…It was observed that patients presented with symptoms such as hoarseness, dysphonia, dysphagia, throat discomfort, cough, weight loss, odynophagia, dyspnea, and sore throat. Hoarseness was the most commonly seen complaint, as also our patient [4][5][6][7][8][9][10][11][12][13][14]. Although concomitant diseases vary, it was seen that one patient was found to be accompanied by retroperitoneal fibrosis which is in the spectrum of IgG4-RD.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Con respecto al compromiso laríngeo, éste es muy poco frecuente, no conociendo su incidencia real. En la actualidad, existen solamente 12 casos reportados en la literatura, los cuales se describen en la Tabla 1 [8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionunclassified